Cytotoxic and antiangiogenic paclitaxel solubilized and permeation-enhanced by natural product nanoparticles. Issue 2 (February 2015) - Liu, Zhijun; Zhang, Fang; Koh, Gar Yee; Dong, Xin; Hollingsworth, Javoris; Zhang, Jian; Russo, Paul S.; Yang, Peiying; Stout, Rhett W.
<x xml:space="preserve">Abstract</x> Paclitaxel (PTX) is one of the most potent intravenous chemotherapeutic agents to date, yet an oral formulation has been problematic because of its low solubility and permeability. Using the recently discovered solubilizing properties of rubusoside (RUB), we investigated the unique PTX–RUB formulation. PTX was solubilized by RUB in water to levels of 1.6–6.3 mg/ml at 10–40% weight/volume. These nanomicellar PTX–RUB complexes were dried to a powder, which was subsequently reconstituted in physiologic solutions. After 2.5 h, 85–99% of PTX–RUB remained soluble in gastric fluid, whereas 79–96% remained soluble in intestinal fluid. The solubilization of PTX was mechanized by the formation of water-soluble spherical nanomicelles between PTX and RUB, with an average diameter of 6.6 nm. Compared with Taxol, PTX–RUB nanoparticles were nearly four times more permeable in Caco-2 cell monocultures. In a side-by-side comparison with dimethyl sulfoxide-solubilized PTX, PTX–RUB maintained the same level of cytotoxicity against three human cancer cell lines with IC50 values ranging from 4 to 20 nmol/l. In addition, tubule formation and migration of human umbilical vein endothelial cells were inhibited at levels as low as 5 nmol/l. These chemical and biological properties demonstrated by the PTX–RUB nanoparticles may improve oral bioavailability and enable further pharmacokinetic, toxicologic, and efficacy investigations.